A truncated splice variant of human lysyl oxidase-like 2 promotes migration and invasion in esophageal squamous cell carcinoma. (June 2016) - Zou, Hai-Ying; Lv, Guo-Qing; Dai, Li-Hua; Zhan, Xiu-Hui; Jiao, Ji-Wei; Liao, Lian-Di; Zhou, Tai-Mei; Li, Chun-Quan; Wu, Bing-Li; Xu, Li-Yan; Li, En-Min
Highlights: We have identified a novel splice variant of lysyl oxidase-like 2, termed LOXL2Δ72. LOXL2Δ72 has the same N- and C-termini as wild-type LOXL2, but lacks 72 nucleotides encoding 24 amino acids. LOXL2Δ72 is no longer secreted, and enzymatic activity is very low. LOXL2Δ72 promotes ESCC cell migration and invasion to a greater degree than LOXL2WT. LOXL2Δ72 may contribute to tumor progression via novel molecular mechanisms. Abstract: Lysyl oxidase-like 2 (LOXL2) is a member of the lysyl oxidase family, which plays an important role in extracellular matrix protein biosynthesis and tumor progression. In the present study, we identified a novel splice variant, LOXL2Δ72, which encodes a peptide having the same N- and C-termini as wild-type LOXL2 (LOXL2WT), but lacks 72 nucleotides encoding 24 amino acids. LOXL2Δ72 had dramatically reduced enzymatic activity, and was no longer secreted. However, LOXL2Δ72 promoted greater cell migration and invasion than LOXL2WT. Furthermore, a dual luciferase reporter assay indicated that LOXL2Δ72 activates distinct signal transduction pathways compared to LOXL2WT, consistent with cDNA microarray data showing different expression levels of cell migration- and invasion-related genes induced following over-expression of each LOXL2 isoform. In particular, LOXL2Δ72 distinctly promoted esophageal squamous cell carcinoma (ESCC) cell migration via up-regulating the C-C motif chemokine ligand 28 (CCL28). Our results suggest that the new LOXL2 splice variant contributes to tumor progression by novel molecular mechanisms different from LOXL2WT.